Development of a Science Learning Assessment Using the Quizwhizzer Application to Measure Digital Literacy of Junior High School Students - Hariyanti, Salsa Alviana Putri; Wicaksono, Iwan; Muhamad Damanhuri, Muhd Ibrahim; Rusdianto, Rusdianto (Journal of Educational Science and Technology (EST), 2025)
Digital literacy can be defined as an attitude in analyzing and evaluating effectively in various learning. Learning in the 21st century requires efforts to adapt to changes due to the rapid advancement of technological knowledge. Digital literacy skills in Indonesia are still classified as moderate with a digital literacy index of 3.49. This study aims to determine the validity of the items, reliability, distinguishing power and level of difficulty by using the quizwhizzer application in measuring digital literacy of junior high school students. This research is a type of development research that refers to the Borg and Gall development model procedure which has several stages including analysis, planning, product design development, validation, product revision, initial trial, and final trial. The results of the expert validity research analysis have an average of 75.4% and all items are declared valid and have a reliability value with an average of 0.636. The analysis of the differentiation and difficulty level of the items was good enough. The conclusion of this development research is a science learning assessment using the quizwhizzer application to measure the digital literacy of junior high school students that is valid, reliable and feasible to use in the evaluation process.